Renoprotective effects of prazosin on ischemia-reperfusion injury in rats. (August 2021) - Rahimi, MM; Bagheri, A; Bagheri, Y; Fathi, E; Bagheri, S; Nia, AV; Jafari, S; Montazersaheb, S
Background: Renal ischemia-reperfusion (IR) injury is one of the main leading causes of acute kidney injury associated with inflammation, oxidative stress and cell apoptosis. We studied the effects of prazosin, as a specific blocker of α1-AR, on renal IR injury. Methods: Rats were divided into normal control; untreated IR and prazosin-treated IR (1 mg/kg body weight). Prazosin was administered by intraperitoneal injection 30 min prior to IR induction. The level of urea/creatinine and oxidative factors were detected by colorimetric methods. Apoptosis-associated factors, inflammatory, and signaling proteins were analyzed in renal tissue. The abnormalities of renal histopathology were detected by immunohistochemistry. Results: Administration of prazosin to IR rats ameliorated serum urea and creatinine and IR-induced histopathological damages. Lipid peroxidation was significantly improved after treatment by prazosin in IR injury rats, however, antioxidant status was not affected. Rats subjected to IR injury activated Bax protein and NF-κB mediated inflammatory response. Moreover, treatment with prazosin inhibited renal NF-κB activation, resulting in a significant decline in pro-inflammatory cytokine of IL-6. Conclusion: These findings suggest that prazosin could be a good candidate to attenuate renal IR injury due to its ability to modulate renal function, apoptosis and inflammation.